Systemic Analysis of RNA Alternative Splicing Signals Related to the Prognosis for Head and Neck Squamous Cell Carcinoma - Li, Zhexuan; Chen, Xun; Wei, Ming; Liu, Guancheng; Tian, Yongquan; Zhang, Xin; Zhu, Gangcai; Chen, Changhan; Liu, Jiangyi; Wang, Tiansheng; Lin, Gongbiao; Wang, Juncheng; et al. (Frontiers in Oncology, 2020)
Alternative splicing (AS) is an important mechanism responsible for the production of protein diversity. Increasing evidence has suggested that the out-of-control alternative splicing is closely related to the genesis and development of cancer. Genome-wide alternative splicing analysis on head and neck squamous cell carcinoma (HNSCC) has not been systemically studied, and so remains at the preliminary stage and requires further studies by researchers. In this study, systemic bioinformatic analysis was carried out on the genome-wide alternative splicing events of 498 clinical HNSCC samples from the TCGA database. In addition, the alternative splicing network was constructed, and 7 potential HNSCC feature genes (NPHP3, TRABD2A, IFT20, TTC39A, CD44, PLS3, and CDDC23) were discovered after web mining and correlation analysis between alternative splicing and gene expression. Finally, these 7 feature genes were verified through multivariate survival model analysis to well classify the prognosis at alternative splicing time and gene expression levels.